Економіко-математичне обґрунтування оцінювання умов КХП до виробничої адаптації - Магомедов, Муса Сергоєвич (НТУ "ХПІ", 2016)
На базі аналізу сучасного стану діяльності вітчизняних коксохімічних підприємств, визначено необхідність проведення виробничої адаптації цих суб’єктів господарювання до наявності відповідних хіміко-технологічних умов виробництва коксу поліпшеної якості. На підставі дослідження фактичних результатів роботи коксохімічних підприємств, наукових статей, звітів галузевих інститутів виявлено основні якісні характеристики коксу за встановленими марками, зроблено їх порівняння з зарубіжними аналогами. На базі проведення експертної оцінки техніко-технологічних показників, зроблено їх ранжування за впливом на якість коксу. За допомогою методу ієрархій встановлено, яке з п’яти коксохімічних підприємств має найкращі позиції у галузевій конкуренції та умови для проведення подальшої виробничої адаптації.

Based on analysis of the current state of activity of the domestic coking enterprises, determined the need for the production of the adaptation of business entities to the presence of the relevant chemical and technological conditions for the production of improved quality of coke. Based on the research results of the actual coke enterprises, research papers, industry institutes reports identified the major quality characteristics of coke on the established brands, made their comparison with foreign analogues. By the previously known technical and technological parameters of quality of coke, have been added to indicators such as: treatment of post-coke and the actual cost of production. Of post-processing of coke by dry quenching it is an important measure as it allows to increase the quality of coke and dispose of its heat. Display the actual cost of coke production characterizes the quality of coke through the cost of coal procurement, which is currently in the domestic enterprise receives either had occupied territory, either from Russia or from foreign countries (USA, Australia, Canada, etc.). A question of experts and ranking of fourteen indicators to influence the quality of the coke. Using the method of the hierarchies established a five-coke enterprises has the best position on the coke quality in industry competition and the conditions for further industrial adaptation.
Economic-mathematical basis of assessment of the CCP to the production conditions of adaptation
Keywords: адаптація виробнича; підприємства коксохімічні; конкуренція галузева; показники хіміко-технологічні; оцінки експертні; метод ієрархій; кокс; якість; adaptation; coke plants; competition; expert assessments; hierarchies method; coke quality